Activation of Coconut Shell through Alkalization Process as a Biochar for Soil Amendment - Gebrina Rizki; Zulnazri Zulnazri; Rozanna Dewi; Rizka Nurlaila; Iqbal Kamar; S. Syafi’ie (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2026)
Based on data from the Central Statistics Agency, most land in Indonesia has experienced degradation. Total area of critical land in Indonesia reaches 9,681,356 hectares, much of which is utilized for plantation activities. One of the regions significantly affected by this condition is Aceh Province, where extensive plantation areas are dominated by ultisol soils. The soil in this area is characterized by acidic conditions, low organic carbon content (approximately 0.5–2%), and moderate to very low total nitrogen levels (<0.50%), indicating inherently low soil fertility. These conditions ultimately result in reduced crop productivity, highlighting the urgent need for sustainable soil amendment strategies that can simultaneously improve soil chemical properties, enhance soil structure, and restore long-term soil fertility. To address this issue, the utilization of biochar derived from biomass waste, such as coconut shells, is considered a promising solution. Biochar has been widely reported as an effective soil amendment capable of mitigating soil degradation, improving soil fertility, and supporting sustainable agricultural systems. However, the effectiveness of biochar is strongly influenced by its physicochemical properties, which are determined by both carbonization conditions and activation methods. In this study, the use of NaOH as an alkaline activator is expected to not only increase biochar surface area and reactive sites but also contribute to soil pH adjustment, which is particularly beneficial for acidic ultisol soils. This study aims to directly evaluate the effect of NaOH-activated biochar on plant growth and analyze the characteristics of the resulting biochar based on SNI 7763:2024. The biochar was produced through a carbonization process with varying residence times of 30, 45, 60, and 75 minutes at a temperature of 300 °C, followed by chemical activation using NaOH solutions with concentrations of 1, 1.5, 2, and 2.5 N for 3 hours to obtain optimal biochar characteristics. The results demonstrated that NaOH-activated biochar had a highly significant effect on plant height. The application of activated biochar improved soil structure by enhancing texture and porosity, reduced soil acidity, and promoted root development, which collectively increased nutrient availability and uptake by plants. The best moisture content and pH were achieved at 75 minutes of carbonization with 2.5 N NaOH, reaching 8.88% and 9.5, respectively. The highest C-Organic content was obtained at 30 minutes of carbonization and 2.5 N NaOH concentration, which was 55.80%. The relatively high C/N ratio indicates that the biochar is highly potential as a soil amendment to enhance soil fertility and crop productivity. Overall, NaOH-activated biochar had a highly significant effect on plant height by improving soil structure and creating more favorable conditions for plant growth.